2013
DOI: 10.1016/j.bmc.2013.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Chrysophaentins are competitive inhibitors of FtsZ and inhibit Z-ring formation in live bacteria

Abstract: The bacterial cell division protein FtsZ polymerizes in a GTP-dependent manner to form a Z-ring that marks the plane of division. As a validated antimicrobial target, considerable efforts have been devoted to identify small molecule FtsZ inhibitors. We recently discovered the chrysophaentins, a novel suite of marine natural products that inhibit FtsZ activity in vitro. These natural products along with a synthetic hemi-chrysophaentin exhibit strong antimicrobial activity toward a broad spectrum of Gram-positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 30 publications
1
55
0
Order By: Relevance
“…52 Keffer et al synthesized hemi-chrysophaentin and found that its mechanism of action was similar to that of chrysophaentin A. 53 Both chrysophaentin A and hemi-chrysophaetin did not exhibit antimicrobial activity against gram-negative bacteria, but inhibited Ec -FtsZ in vitro , which could be ascribed to these compounds’ inability to pass through the outer membrane of gram-negative bacteria. Thus, in order to test this hypothesis, the activities of chrysophaentin A and hemi-chrysophaetin were determined against E. coli envA1 , a strain with increased compound permeability, and found the IC 50 values to be 27 μM and 84 μM, respectively, which proved the hypothesis.…”
Section: Ftsz Inhibitorsmentioning
confidence: 99%
“…52 Keffer et al synthesized hemi-chrysophaentin and found that its mechanism of action was similar to that of chrysophaentin A. 53 Both chrysophaentin A and hemi-chrysophaetin did not exhibit antimicrobial activity against gram-negative bacteria, but inhibited Ec -FtsZ in vitro , which could be ascribed to these compounds’ inability to pass through the outer membrane of gram-negative bacteria. Thus, in order to test this hypothesis, the activities of chrysophaentin A and hemi-chrysophaetin were determined against E. coli envA1 , a strain with increased compound permeability, and found the IC 50 values to be 27 μM and 84 μM, respectively, which proved the hypothesis.…”
Section: Ftsz Inhibitorsmentioning
confidence: 99%
“…FtsZ has been validated as the target of the in vivo effective antibacterial compound PC190723 (7), which modulates FtsZ assembly by stabilizing its polymers (8,9) and binds into the cleft between the C-terminal domain and the core helix H7 of this protein (9)(10)(11). Moreover, several nucleotide analogs (12,13) and nonnucleotide compounds that selectively target the nucleotide site of FtsZ have also been identified (14)(15)(16).…”
Section: Introductionmentioning
confidence: 97%
“…NMR experiments further demonstrated that chrysophaentin A 18 occludes a large portion of the GTP-binding site of FtsZ, which may explain its mechanism of action [72]. Hemichrysophaentin 19 also inhibits the GTPase activity of both organisms (E. coli IC 50 37 ± 7 μM; S. aureus 38 ± 9 μM) [102]. Hemichrysophaentin 19 competes with GTP for binding to the FtsZ nucleotide pocket and, like chrysophaentin A, decreases the polymerization of FtsZ, resulting in the disruption of Z-ring localization and integrity.…”
Section: Phenols -Chrysophaentin a 18mentioning
confidence: 94%